Hydrophilic copolymer and hydrophilic composition

By using a specific hydrophilicity cluster, using the cross -linking response of its structural unit, the problem of lack of water resistance and thermal heat resistance in existing technologies, and realizing high -performance hydrophilicity and anti -foggy coating membrane.

CN119384439APending Publication Date: 2025-01-28SHIN ETSU CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380042892.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-04-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the water resistance and heat resistance of the hydrophilic coating film are insufficient, and it is easy to dissolve after contact with water, resulting in deterioration of surface characteristics and loss of anti-fog properties under high temperature environments.

Method used

A specific hydrophilic symbol is used, which consists of a structural unit (A) and a structural unit (B), and through the binary of amino -based keratonate bonds, pyrine bonds, sulfate amino -based keys and sulfur bond bonds, and sulfur bond bonds Connect the group for cross -linking to form coating films with water resistance and heat resistance.

Benefits of technology

A coating film with excellent water resistance, hydrophilic and anti -fog -resistant coating film that can give continuous and heat -resistant coating films with excellent water resistance, organic and heat -resistant performance degradation in water contact and high temperature environment can be avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384439A_ABST
    Figure CN119384439A_ABST
Patent Text Reader

Abstract

A hydrophilic copolymer comprising a structural unit (a) represented by formula (1) and a structural unit (b) represented by formula (2) forms a coating film having excellent hydrophilicity and antifogging properties. (In formula (1), R1 represents a hydrogen atom or a methyl group, R2 represents-(C2H4O) m-R6 or-(C3H6O) m-R6, m represents an integer of 1-50, R6 represents a hydrogen atom or an alkyl group having 1-6 carbon atoms, X1 represents a divalent linking group, in formula (2), R3 represents a hydrogen atom or a methyl group, R4 and R5 each independently represent an alkyl group having 1-10 carbon atoms or an aryl group having 6-10 carbon atoms, X2 represents a divalent linking group, n represents an integer of 1-3, and n represents an integer of 1-3. And star number * represents a bond to an adjacent structural unit. > # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrophilic copolymer and a hydrophilic composition containing the hydrophilic copolymer. Background Art

[0002] In recent years, there has been an increasing demand for improvement in the blurring of substrates formed of organic materials such as plastics and inorganic materials such as glass.

[0003] The improvement of the blurring of the substrate is generally achieved by coating a hydrophilic film on the surface of the substrate. For example, in Patent Document 1, a coating composition to which a hydrophilic copolymer having a quaternary ammonium salt structure with high hydrophilicity is added is proposed as a coating agent capable of imparting hydrophilicity to the substrate.

[0004] However, the coating film formed by using the above coating composition has insufficient water resistance, and after contact with water, a part of the hydrophilic composition in the coating film is dissolved, and the surface properties such as hydrophilicity and anti-fogging properties are sometimes deteriorated. If such a part dries, water dripping marks may remain on the coating film.

[0005] Furthermore, the heat resistance is also insufficient, and the antifogging property of the coating film may disappear after being left to stand in an environment of 120° C. for 24 hours.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-162431 Summary of the invention

[0009] Problems to be solved by the invention

[0010] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a hydrophilic copolymer that forms a coating film having excellent hydrophilicity and antifogging properties, and a hydrophilic composition containing the same.

[0011] Means for solving problems

[0012] The present inventors have conducted intensive studies to achieve the above-mentioned object and have found that a specific hydrophilic copolymer can form a coating film having excellent water resistance and imparting hydrophilicity and antifogging properties having durability and heat resistance to substrates formed of organic materials such as plastics and inorganic materials such as glass, thereby completing the present invention.

[0013] That is, the present invention provides:

[0014] 1. A hydrophilic copolymer comprising a structural unit (a) represented by the following formula (1) and a structural unit (b) represented by the following formula (2),

[0015] [Chemistry 1]

[0016]

[0017] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 Represents -(C2H4O) m -R 6 or -(C3H6O) m -R 6 , m represents an integer from 1 to 50, R 6 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, X 1 represents a divalent linking group,

[0018] In formula (2), R 3 represents a hydrogen atom or a methyl group, R 4 and R 5 Each independently represents an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms, and X 2 represents a divalent linking group, n represents an integer of 1 to 3, and the asterisk * represents a bond to an adjacent structural unit;

[0019] 2. The hydrophilic copolymer according to 1, wherein the X 1 and X 2 Each independently is a divalent linking group having one or more selected from a carbamate bond, a urea bond, a thiourethane bond, and a thiourea bond;

[0020] 3. A hydrophilic composition comprising the hydrophilic copolymer according to 1 or 2;

[0021] 4. A film formed by curing the hydrophilic composition according to 3.

[0022] Effects of the Invention

[0023] The hydrophilic copolymer of the present invention forms a hydrophilic composition which can form a coating film having excellent water resistance and capable of imparting hydrophilicity and antifogging properties with durability and heat resistance to organic substrates such as plastics and inorganic substrates such as glass. DETAILED DESCRIPTION

[0024] The present invention will be described in detail below.

[0025] [1] Hydrophilic copolymer

[0026] The hydrophilic copolymer according to the present invention (hereinafter also simply referred to as “copolymer”) comprises the structural unit (a) and the structural unit (b) described below.

[0027] The structural units of the hydrophilic copolymer according to the present invention are described below.

[0028] The structural unit (a) contained in the hydrophilic copolymer of the present invention is represented by the following formula (1).

[0029] [Chemistry 2]

[0030]

[0031] (In the formula, the asterisk * has the same meaning as above.)

[0032] In formula (1), R 1 It is a hydrogen atom or a methyl group, and is preferably a hydrogen atom.

[0033] R 2 -(C2H4O) m -R 6 or -(C3H6O) m -R 6 m is an integer of 1-50, preferably an integer of 2-10, and more preferably an integer of 2-5.

[0034] R 6 is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. The alkyl group having 1 to 6 carbon atoms may be any of linear, branched, and cyclic, and specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, and cyclohexyl.

[0035] Among these, R 6 It is preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and still more preferably a methyl group.

[0036] As R 2 Specific examples of include groups represented by the following formulae, but are not limited to these.

[0037] [Chemistry 3]

[0038]

[0039] X 1 The divalent linking group is not particularly limited, but preferably has one or more divalent linking groups selected from carbamate bonds, urea bonds, thiocarbamate bonds and thiourea bonds, and more preferably -(CH2) k1 -Z-(CH2) k2 -(Z represents a urethane bond, a urea bond, a thiourethane bond or a thiourea bond, and k1 and k2 each independently represent an integer of 1 to 5, preferably 2 to 4.) A connecting group represented by.

[0040] As X 1Specific examples of the divalent linking group include groups represented by the following formulae, but are not limited to these.

[0041] [Chemistry 4]

[0042]

[0043] Specific examples of the structural unit (a) represented by the above formula (1) include structural units represented by the following formulae, but are not limited to these.

[0044] [Chemistry 5]

[0045]

[0046] (In the formula, the asterisk * has the same meaning as above.)

[0047] The structural unit (b) contained in the hydrophilic copolymer of the present invention is represented by the following formula (2).

[0048] The hydrolyzable silyl group contained in the structural unit (b) can undergo a crosslinking reaction (self-crosslinking) by itself, thereby forming a crosslinked structure including a hydrophilic copolymer in the coating film.

[0049] [Chemistry 6]

[0050]

[0051] (In the formula, the asterisk * has the same meaning as above.)

[0052] In formula (2), R 3 It is a hydrogen atom or a methyl group, and is preferably a methyl group.

[0053] R 4 and R 5 Each independently represents an alkyl group having 1 to 10 carbon atoms, preferably 1 to 8 carbon atoms, and more preferably 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms, preferably 6 to 8 carbon atoms.

[0054] As R 4 and R 5 The alkyl group may be linear, branched or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl and cyclohexyl.

[0055] As R 4 and R 5 Specific examples of the aryl group include phenyl and tolyl.

[0056] Among these, R 4Preferably, it is an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group. 5 An alkyl group having 1 to 3 carbon atoms is preferred, and a methyl group or an ethyl group is more preferred.

[0057] n represents an integer of 1 to 3, and 3 is preferred.

[0058] X 2 The divalent linking group is not particularly limited, but preferably has one or more divalent linking groups selected from carbamate bonds, urea bonds, thiocarbamate bonds and thiourea bonds, and more preferably -(CH2) k1 -Z-(CH2) k2 -(Z represents a urethane bond, a urea bond, a thiourethane bond or a thiourea bond, and k1 and k2 each independently represent an integer of 1 to 5, preferably 2 to 4.) A connecting group represented by.

[0059] As X 2 Specific examples of the divalent linking group include groups represented by the following formulae, but are not limited thereto. Among these, groups containing a urea bond represented by formula (3) are preferred.

[0060] [Chemistry 7]

[0061]

[0062] Specific examples of the structural unit (b) represented by the above formula (2) include structural units represented by the following formulae, but are not limited to these.

[0063] [Chemistry 8]

[0064]

[0065] (In the formula, the asterisk * has the same meaning as above.)

[0066] In the hydrophilic copolymer of the present invention, the content of the structural unit (a) is preferably 20 to 99% by mass, more preferably 50 to 95% by mass, and further preferably 60 to 90% by mass. If the content of the structural unit (a) is 20% by mass or more, the hydrophilicity of the copolymer becomes better, and the hydrophilicity of the coating film when the coating film is formed becomes better. On the other hand, when the content of the structural unit (a) is 95% by mass or less, the hydrophilicity of the copolymer does not increase excessively, and the water resistance of the coating film when the coating film is formed becomes good.

[0067] The content of the structural unit (b) is preferably 1 to 80% by mass, more preferably 5 to 50% by mass, and further preferably 10 to 40% by mass.

[0068] The total content of the structural unit (a) and the structural unit (b) in the hydrophilic copolymer of the present invention is preferably 51 to 100% by mass, more preferably 80 to 100% by mass, and even more preferably 90 to 100% by mass.

[0069] The hydrophilic copolymer of the present invention may contain a structural unit (c) represented by the following formula (4) in addition to the structural unit (a) and the structural unit (b) described above.

[0070] [Chemistry 9]

[0071]

[0072] (In the formula, the asterisk * has the same meaning as above.)

[0073] In the above formula (4), R 7 It is a hydrogen atom or a methyl group, preferably a methyl group.

[0074] X 3 It is -NH- or -O-, preferably -O-.

[0075] Y 1 It is a group selected from a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, an isocyanate group, an epoxy group, an alkoxy group (—OR) and a hydrolyzable silyl group.

[0076] As Y 1 The alkyl group of R may be a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and specific examples thereof include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, tert-butoxy, n-pentoxy, n-hexyloxy, cyclopentyloxy, cyclohexyloxy, etc. In addition, part or all of the hydrogen atoms bonded to the carbon atom of the alkyl group of R may be substituted with halogen atoms such as chlorine, fluorine, and bromine, or other substituents such as cyano.

[0077] As Y 1 The hydrolyzable silyl group includes, for example, alkoxysilyl groups such as trimethoxysilyl, triethoxysilyl, dimethoxysilyl, diethoxymethylsilyl, monomethoxydimethylsilyl and monoethoxydimethylsilyl; carboxylate silyl groups such as acetoxysilyl; halogenated silyl groups such as trichlorosilyl, dichlorosilyl and monochlorosilyl; aminosilyl; oxime silyl; hydrosilyl and the like.

[0078] Among these, Y 1 Preferred are a hydrogen atom and a hydroxyl group.

[0079] j is an integer of 0 to 10, preferably an integer of 0 to 6, more preferably an integer of 1 to 4, and further preferably an integer of 2 to 4.1 A hydrogen atom.

[0080] In the case where the hydrophilic copolymer of the present invention contains the structural unit (c), for example, if the copolymer of the present invention and a Y having a Y 1 The functional group of the cross-linking reaction is used together with a curing agent, and a cross-linked structure can be formed by the curing agent and the copolymer. In addition, for example, if the copolymer of the present invention is used together with a curing catalyst such as an acid catalyst, the copolymer itself can also carry out a cross-linking reaction (self-crosslinking). Therefore, the coating film formed by the composition comprising the hydrophilic copolymer of the present invention and the curing agent has a cross-linked structure and can play an excellent water resistance.

[0081] From this perspective, in the above formula (4), Y 1 More preferably, hydroxyl groups are present. 1 In the case of the structural unit (c) being a hydroxyl group, for example, by combining the copolymer of the present invention with a curing agent having an isocyanate group, a crosslinked structure can be formed even under low temperature conditions (e.g., below 110° C.). Therefore, a coating film formed from the composition of the present invention can be formed even on a substrate having low heat resistance.

[0082] Specific examples of the structural unit (c) represented by the above formula (4) include structural units represented by the following formulae, but are not limited to these.

[0083] [Chemistry 10]

[0084]

[0085] (In the formula, the asterisk * has the same meaning as above.)

[0086] When the hydrophilic copolymer of the present invention contains the structural unit (c), the content thereof is not particularly limited, but is preferably 1 to 50% by mass, more preferably 3 to 20% by mass, and further preferably 5 to 10% by mass.

[0087] The order of the structural units contained in the hydrophilic copolymer of the present invention is arbitrary, and the copolymer of the present invention may be any of an alternating copolymer, a random copolymer, and a block copolymer.

[0088] The weight average molecular weight of the hydrophilic copolymer of the present invention is not particularly limited, but is preferably 1000 to 1000000, more preferably 5000 to 700000, further preferably 300000 to 600000, and further preferably 400000 to 500000, from the viewpoint of improving affinity with organic solvents and hardness of the coating film. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) (standard substance: polystyrene, elution solvent: tetrahydrofuran).

[0089] The viscosity of the hydrophilic copolymer of the present invention is not particularly limited, but is preferably 0.01 to 0.5 Pa·s (temperature 25° C.) from the viewpoint of compatibility with organic solvents and workability. The viscosity is a value measured using a B-type rotational viscometer.

[0090] The glass transition temperature of the hydrophilic copolymer is preferably -10 to 50° C. The glass transition temperature is a value measured in accordance with JIS K7121.

[0091] The hydrophilic copolymer of the present invention can be obtained by a known method. For example, as shown in the following scheme, it can be obtained by polymerizing a polymerizable monomer containing an isocyanate group represented by the following formula (5) in the presence of a polymerization initiator under an inert gas atmosphere such as nitrogen, and then reacting an amino alcohol represented by the following formula (6) and an organosilicon compound represented by the following formula (7) under an air atmosphere or an inert gas atmosphere such as nitrogen.

[0092] [Chemistry 11]

[0093]

[0094] It should be noted that in the above formulas, R 1 ~R 5 , X 1 , X 2 and n represent the same meanings as above. h represents an integer of 1 to 10, g represents an integer of 1 to 3, and Y 2 represents a functional group selected from -NH(R'), -SH and -OH, R' represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and a, b and c are values ​​such that the content of each structural unit falls within the above range.

[0095] Examples of the alkyl group having 1 to 6 carbon atoms include the same ones as mentioned above.

[0096] As the polymerizable monomer containing an isocyanate group of the formula (5), a commercially available item can be used, and examples thereof include KARENZ (registered trademark) AOI manufactured by Showa Denko KK.

[0097] The polymerization initiator is preferably a thermal polymerization initiator, and the amount of the polymerization initiator added is preferably 0.5 to 30% by mass, more preferably 1 to 20% by mass, and further preferably 2 to 10% by mass relative to the total mass of the copolymerized monomers. The polymerization initiator may be added all at once or in divided portions.

[0098] Specific examples of the compound represented by the above formula (7) are shown below, but the present invention is not limited thereto. Among these, the compound represented by (8) is preferred.

[0099] [Chemistry 12]

[0100]

[0101] (In the formula, Me represents a methyl group and Et represents an ethyl group.)

[0102] The above reaction can be carried out without a solvent, and can be carried out in an organic solvent such as methyl ethyl ketone, 1,2-dimethoxyethane, etc., as necessary, within a range that does not inhibit the reaction.

[0103] The reaction temperature is preferably 0° C. to the boiling point of each solvent, and more preferably 20 to 80° C. The reaction time is preferably 1 to 24 hours, and more preferably 5 to 10 hours.

[0104] The hydrophilic copolymer obtained by the above method can be mixed with additives as needed after adjusting the solid content concentration or performing solvent exchange or filtering. In addition, the hydrophilic copolymer produced by polymerization can be purified by precipitation or reprecipitation using hexane or the like, and dissolved in a solvent suitable for the purpose together with the additives.

[0105] [2] Hydrophilic composition

[0106] The hydrophilic composition of the present invention (hereinafter also referred to as "composition") contains one or more of the above-mentioned hydrophilic copolymers. The content of the hydrophilic copolymer contained in the composition of the present invention is not particularly limited, but from the viewpoint of hydrophilicity, it is preferably 1 to 50% by mass of the entire composition, and more preferably 5 to 25% by mass.

[0107] The composition of the present invention may contain other additives and the like within a range not impairing the object of the present invention.

[0108] Other additives include acids such as hydrochloric acid, sulfuric acid, nitric acid, acetic acid, formic acid, oxalic acid, and maleic acid; bases such as ammonia, methylamine, and ethylamine; organic metal salts; Lewis acids; alkyl tin ester compounds; leveling agents; surfactants, etc. Among these, by adding organic metal salts, curing at 25°C and 50% RH can be achieved, and a highly durable hydrophilic film can be obtained.

[0109] The leveling agent and surfactant are substances contained in order to improve the uniformity of the coating film, and known substances can be used. In particular, commercial products are preferred because they are easily available.

[0110] Examples of the organic metal salt include sodium acetate, potassium acetate, sodium propionate, potassium propionate, sodium formate, potassium formate, and tin octylate.

[0111] Specific examples of the Lewis acid include tetraisopropyl titanate, tetrabutyl titanate, triisobutoxyaluminum, triisopropoxyaluminum, aluminum acetylacetonate, tin chloride (SnCl 4 ), titanium chloride (TiCl 4 ), zinc chloride (ZnCl 4 ), and the like.

[0112] Specific examples of the alkyl tin ester compound include alkyl tin ester compounds such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dioctoate, dioctyltin dioctoate, and dioctyltin diversocarbonate.

[0113] These may be used alone or in combination of two or more.

[0114] When the composition of the present invention contains an organic metal salt, the content thereof is preferably 0.05 to 50 parts by mass, more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the hydrophilic copolymer.

[0115] The hydrophilic composition of the present invention may contain a solvent as required. The solvent is not particularly limited as long as it can dissolve or disperse the hydrophilic copolymer and other additives, does not react with the components, and can be easily removed in the drying step described below.

[0116] Specific examples of the solvent include methanol, ethanol, isopropanol, tetrahydrofuran, cyclohexanone, methyl ethyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, 2-methoxyethyl acetate, diethylene glycol dimethyl ether, 1-methoxy-2-propanol, 1-methoxy-2-propyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, toluene, ethyl acetate, ethyl lactate, methyl lactate, dimethyl sulfoxide, water, and the like.

[0117] These may be used alone or in combination of two or more.

[0118] The solid content concentration of the composition of the present invention is preferably 5 to 80% by mass, more preferably 10 to 30% by mass, from the viewpoint of coating properties and workability.

[0119] The viscosity of the composition of the present invention is preferably 0.01 to 0.05 Pa·s (temperature 25° C.) from the viewpoint of coating properties and workability.

[0120] The composition of the present invention may be a one-component type or may be a type in which two or more components are mixed before use.

[0121] The composition of the present invention can impart hydrophilicity to various substrates by being applied to the substrates.

[0122] Specific examples of materials constituting the above-mentioned substrate include glass; synthetic resins {polymethyl methacrylate resin, polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, ABS resin, polycarbonate resin, polystyrene resin, epoxy resin, unsaturated polyester resin, melamine resin, diallyl phthalate resin, polyimide resin, polyurethane resin, nylon resin, polyethylene resin, polypropylene resin, polyvinyl chloride resin, fluororesins (polytetrafluoroethylene resin, polychlorotrifluoroethylene resin, polyvinylidene fluoride resin, perfluoroalkoxy fluororesin, tetrafluoroethylene-hexafluoropropylene copolymer resin, ethylene tetrafluoroethylene copolymer resin, ethylene-chlorotrifluoroethylene resin); fluoroethylene copolymer resin, etc.), polybutadiene, polyisoprene, SBR, nitrile rubber, EPM, EPDM, epichlorohydrin rubber, chloroprene rubber, polysulfide, butyl rubber, etc.}; metals (iron, aluminum, stainless steel, titanium, copper, brass, alloys thereof, etc.); cellulose, cellulose derivatives, cellulose analogs (chitin, chitosan, metalloporphyrin, etc.), natural fibers such as cotton, silk, wool, regenerated fibers such as rayon, semi-synthetic fibers such as acetate, synthetic fibers such as vinylon, polyester, nylon, polyethylene, polypropylene, polyurethane, aramid fibers, etc.; composite fibers of these fibers (polyester / cotton, etc.), etc., as their forms, there can be listed substrates, sheets, films, fibers, various articles using them, etc.

[0123] The composition of the present invention is applied onto a surface of a substrate or the like to form a coating film, which can be a hydrophilic coating film.

[0124] Examples of coating methods include rod coating, dip coating, spin coating, spray coating, flow coating, brush coating, gravure coating, roll transfer, knife coating, air knife coating, slit coating, screen coating, inkjet, and flexographic printing. Among these, rod coating is preferred.

[0125] After applying the composition on a substrate, the composition is allowed to stand at room temperature in the atmosphere to obtain a cured coating film. The standing time is preferably 12 to 240 hours, more preferably 24 to 120 hours.

[0126] In order to shorten the curing process, heating may be performed.

[0127] In this case, the heating temperature is preferably 40 to 250°C, more preferably 80 to 120°C.

[0128] The heating time is preferably 10 seconds to 12 hours, more preferably 30 seconds to 3 hours.

[0129] The heating atmosphere may be any of an air atmosphere and an inert gas (eg, nitrogen, argon, etc.) atmosphere.

[0130] The thickness of the coating film (dry film thickness) is not particularly limited, but is preferably 0.1 to 50 μm, more preferably 1 to 20 μm.

[0131] Example

[0132] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0133] (1) Production of hydrophilic copolymers

[0134] [Example 1-1]

[0135] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the following formula (9), and 0.72 g of an oil-soluble azo polymerization initiator V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) represented by the following formula (10) were added to a reactor and reacted at 80°C for 4 hours.

[0136] Next, 30.64 g of diethylene glycol monomethyl ether, 8.07 g of 3-aminopropyltrimethoxysilane, and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0137] After the reaction, the heating of the reaction container was stopped, and after the temperature of the solution in the reaction container became below 25° C., filtration was performed to obtain 164 g (solid content concentration 43% by mass) of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P1 (content of structural unit (a) 85.0% by mass, content of structural unit (b) 15.0% by mass; weight average molecular weight 440,000).

[0138] [Chemistry 13]

[0139]

[0140] [Example 1-2]

[0141] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 0.72 g of an oil-soluble azo polymerization initiator V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added to a reactor and reacted at 80°C for 4 hours.

[0142] Next, 40.01 g of dipropylene glycol monomethyl ether, 5.38 g of 3-aminopropyltrimethoxysilane, and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0143] After the reaction, the heating of the reaction container was stopped, and after the temperature of the solution in the reaction container became below 25° C., filtration was performed to obtain 176 g (solid content concentration 44% by mass) of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P2 (content of structural unit (a) 90.0% by mass, content of structural unit (b) 10.0% by mass; weight average molecular weight 480,000).

[0144] [Examples 1-3]

[0145] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 0.72 g of an oil-soluble azo polymerization initiator V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added to a reactor and reacted at 80°C for 4 hours.

[0146] Next, 82.50 g of Uniox (registered trademark) M-550 (manufactured by NOF Corporation, average molecular weight 550) represented by the following formula (11), 26.89 g of 3-aminopropyltrimethoxysilane, and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0147] After the reaction, the heating of the reaction container was stopped, and after the temperature of the solution in the reaction container became below 25° C., filtration was performed to obtain 234 g (solid content concentration 58% by mass) of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P3 (content of structural unit (a) 50.0% by mass, content of structural unit (b) 50.0% by mass; weight average molecular weight 690,000).

[0148] [Chemistry 14]

[0149] CH3—O—(C2H4O) n -H (11)

[0151] [Examples 1-4]

[0152] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 0.72 g of an oil-soluble azo polymerization initiator V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added to a reactor and reacted at 80°C for 4 hours.

[0153] Next, the heating of the reaction container was stopped, and 90.00 g of Uniox (registered trademark) M-1000 (manufactured by NOF Corporation, average molecular weight 1000) represented by the above formula (11), 37.65 g of 3-aminopropyltrimethoxysilane, and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0154] After the reaction, the temperature of the solution in the reaction container became below 25° C. and then the solution was filtered to obtain 257 g (solid content concentration 59% by mass) of a 1,2-dimethoxyethane solution of a hydrophilic copolymer P4 (content of structural unit (a) 30.0% by mass, content of structural unit (b) 70.0% by mass; weight average molecular weight 980,000).

[0155] [Examples 1-5]

[0156] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 0.72 g of V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), an oil-soluble azo polymerization initiator represented by the above formula (10), were added to a reactor and reacted at 80°C for 4 hours.

[0157] Next, 30.64 g of diethylene glycol monomethyl ether, 8.84 g of 3-mercaptotrimethoxymethylsilane, and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0158] After the reaction, the heating of the reaction container was stopped, and after the temperature of the solution in the reaction container became below 25° C., filtration was performed to obtain 165 g (solid content concentration 44% by weight) of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P5 (content of structural unit (a) 85.0% by weight, content of structural unit (b) 15.0% by weight; weight average molecular weight 460,000).

[0159] [Examples 1-6]

[0160] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 0.72 g of V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), an oil-soluble azo polymerization initiator represented by the above formula (10), were added to a reactor and reacted at 80°C for 4 hours.

[0161] Next, 30.64 g of diethylene glycol monomethyl ether, 7.35 g of 3-aminopropyldimethoxymethylsilane, and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0162] After the reaction, the heating of the reaction container was stopped, and after the temperature of the solution in the reaction container became below 25° C., filtration was performed to obtain 162 g (solid content concentration 43% by mass) of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P6 (content of structural unit (a) 85.0% by mass, content of structural unit (b) 15.0% by mass; weight average molecular weight 450,000).

[0163] [Comparative Example 1-1]

[0164] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 0.72 g of V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), an oil-soluble azo polymerization initiator represented by the above formula (10), were added to a reactor and reacted at 80°C for 4 hours.

[0165] Next, 36.05 g of diethylene glycol monomethyl ether and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0166] After the reaction, the heating of the reaction container was stopped, and after the temperature of the solution in the reaction container became below 25°C, filtration was performed to obtain 166 g (solid content concentration 43% by mass) of a 1,2-dimethoxyethane solution of a hydrophilic polymer P7 (content of structural unit (a) 100.0% by mass; weight average molecular weight 490,000).

[0167] [Comparative Example 1-2]

[0168] 100.47 g of 1,2-dimethoxyethane, 42.34 g of KARENZ (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 0.72 g of V-59 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), an oil-soluble azo polymerization initiator represented by the above formula (10), were added to a reactor and reacted at 80°C for 4 hours.

[0169] Next, 8.17 g of methanol, 8.07 g of 3-aminopropyltrimethoxysilane, and 0.15 g of NEOSTANN U-830 (manufactured by Nitto Kasei Co., Ltd.) as a dioctyltin catalyst were added, and the mixture was reacted at 70°C for 4 hours.

[0170] After the reaction, the heating of the reaction container was stopped, and after the temperature of the solution in the reaction container reached 25° C. or less, filtration was performed to obtain 146 g (solid content concentration: 41% by mass) of a 1,2-dimethoxyethane solution of copolymer P8 (weight average molecular weight: 400,000).

[0171] (2) Production of coating composition (hydrophilic composition)

[0172] [Example 2-1]

[0173] 1.16 g of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P1 obtained in Example 1-1, 0.84 g of isopropyl alcohol, and 0.02 g of a titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a reactor to obtain a yellow transparent liquid (C1).

[0174] [Example 2-2]

[0175] 0.86 g of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P2 obtained in Example 1-2, 1.14 g of isopropyl alcohol, and 0.02 g of a titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a reactor to obtain a yellow transparent liquid (C2).

[0176] [Example 2-3]

[0177] 0.85 g of a methyl ethyl ketone solution of the hydrophilic copolymer P3 obtained in Example 1-3, 1.15 g of isopropyl alcohol, and 0.02 g of a titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a reactor to obtain a yellow transparent liquid (C3).

[0178] [Examples 2-4]

[0179] 0.85 g of a methyl ethyl ketone solution of the hydrophilic copolymer P4 obtained in Example 1-4, 1.15 g of isopropyl alcohol, and 0.02 g of a titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a reactor to obtain a yellow transparent liquid (C4).

[0180] [Example 2-5]

[0181] 1.14 g of a methyl ethyl ketone solution of the hydrophilic copolymer P5 obtained in Example 1-5, 0.86 g of isopropyl alcohol, and 0.02 g of a titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a reactor to obtain a yellow transparent liquid (C5).

[0182] [Example 2-6]

[0183] 1.16 g of a methyl ethyl ketone solution of the hydrophilic copolymer P6 obtained in Example 1-6, 0.84 g of isopropyl alcohol, and 0.02 g of a titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a reactor to obtain a yellow transparent liquid (C6).

[0184] [Comparative Example 2-1]

[0185] 1.16 g of the methyl ethyl ketone solution of the hydrophilic polymer P6 obtained in Comparative Example 1-1 and 0.84 g of isopropyl alcohol were added to the reactor to obtain a yellow transparent liquid (C7).

[0186] [Comparative Example 2-2]

[0187] 1.22 g of an ethyl acetate solution of the polymer P7 obtained in Comparative Example 1-2, 0.78 g of isopropyl alcohol, and 0.02 g of a titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a reactor to obtain a yellow transparent liquid (C8).

[0188] [Comparative Example 2-3]

[0189] In a reactor, 10 g of Acryt 6BF-100 (solid content concentration 40% by mass, manufactured by Daisei Fine Chemical Co., Ltd.), a hydroxyl-containing acrylic resin having a weight average molecular weight of 75,000, a hydroxyl value of 20 mgKOH / g and a calculated glass transition temperature of 85°C, 0.65 g of Duranate TPA-100 (NCO content 23% by mass, manufactured by Asahi Kasei Corporation), 1.0 g of a methyl ethyl ketone solution (solid content concentration 40% by mass) of Acryt 1WX (manufactured by Daisei Fine Chemical Co., Ltd.), which is a copolymer containing structural units represented by the following formulae (12), (13), (14), (15) and (16), and 13.6 g of methyl ethyl ketone were mixed to obtain a yellow transparent liquid (C9).

[0190] [Chemistry 15]

[0191]

[0192] (In the formula, the asterisk * has the same meaning as above.)

[0193] (3) Preparation and evaluation of coating films

[0194] [Examples 3-1 to 3-6, Comparative Examples 3-1 to 3-3]

[0195] The coating compositions C1 to C9 obtained in Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-3 were applied to a polycarbonate plate using a bar coater (No. 14), and immediately thereafter dried at 120° C. for 1 hour to obtain a coating film.

[0196] [Examples 4-1 to 4-6, Comparative Examples 4-1 to 4-3]

[0197] The coating compositions C1 to C9 obtained in Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-3 were applied to polycarbonate plates using a bar coater (No. 14) and allowed to stand for 24 hours in an environment of 25° C. and 50% RH to obtain films.

[0198] The following tests were performed on the films produced in the above-mentioned Examples and Comparative Examples. The results are shown in Tables 1 and 2.

[0199] [Anti-fog properties]

[0200] The above-mentioned films were breathed, and the case where the film surface was fogged was marked as ×, and the case where there was no fogging was marked as ○. Furthermore, the film was placed on a 40°C warm water bath at a height of 3 cm from the water surface for 60 seconds, and the case where there was no fogging on the film surface was marked as ◎ to evaluate the anti-fogging property.

[0201] [Water hanging traces]

[0202] After the coating film was left standing for 60 seconds on a 40°C warm water bath in the above anti-fogging evaluation and subjected to anti-fogging evaluation, it was naturally dried at 25°C for 10 minutes, and then the surface was illuminated with a flashlight of 1000 lm to visually check whether there was any water dripping mark on the coating film surface. The case where water dripping mark was found was recorded as +, and the case where no water dripping mark was found was recorded as -.

[0203] [Hot water resistance]

[0204] Each of the above films was immersed in warm water at 40° C. for 24 hours, and the surface water was absorbed with a wipe, followed by natural drying at 25° C. for 10 minutes, and the above antifogging property was evaluated.

[0205] Next, each film was further immersed in warm water at 40°C for 216 hours, and the surface water was absorbed with a wipe, followed by natural drying at 25°C for 10 minutes, and the above-mentioned antifogging property was evaluated.

[0206] [Moisture resistance]

[0207] Each of the above films was allowed to stand for 24 hours in a thermostatic chamber (KCL-2000W, Tokyo Rikaki Co., Ltd.) set at 50°C and 98% RH, and then naturally dried at 25°C for 10 minutes, and the above antifogging property was evaluated.

[0208] [Heat resistance]

[0209] Each of the above films was allowed to stand for 24 hours in a thermostat (SPHH-201, ESPEC Corporation) set at 120° C. Then, the films were allowed to stand at 25° C. for 10 minutes, and the above anti-fogging properties were evaluated.

[0210] [Table 1]

[0211]

[0212] [Table 2]

[0213]

[0214] As shown in Tables 1 and 2, it can be seen that the films of Examples 3-1 to 3-6 and Examples 4-1 to 4-6 maintain excellent anti-fogging properties even after the warm water resistance test (24 hours immersion, 240 hours immersion) and the moisture resistance test (50°C, 98% RH, 24 hours) and the heat resistance test (120°C, 24 hours). In particular, it can be seen that the film of Example 3-1 has excellent durability.

[0215] On the other hand, it can be seen that the anti-fogging properties of the films of Comparative Examples 3-1, 3-3, 4-1 and 4-3 disappeared after immersion in warm water for 24 hours, and these films have poor water resistance. In addition, it can be seen that the anti-fogging properties of the film of Comparative Example 4-1 disappeared after the heat resistance test, and the heat resistance is poor.

Claims

1. A hydrophilic copolymer comprising a structural unit (a) represented by the following formula (1) and a structural unit (b) represented by the following formula (2), [Chemistry 1] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 Represents -(C2H4O) m -R 6 or -(C3H6O) m -R 6 , m represents an integer from 1 to 50, R 6 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, X 1 represents a divalent linking group, In formula (2), R 3 represents a hydrogen atom or a methyl group, R 4 and R 5 Each independently represents an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms, and X 2 represents a divalent linking group, n represents an integer of 1 to 3, and an asterisk * represents a bond to an adjacent structural unit.

2. The hydrophilic copolymer according to claim 1, wherein The X 1 and X 2 Each is independently a divalent linking group having one or more selected from a urethane bond, a urea bond, a thiourethane bond, and a thiourea bond.

3. A hydrophilic composition comprising the hydrophilic copolymer according to claim 1 or 2.

4. A film formed by curing the hydrophilic composition according to claim 3.

Citation Information

Patent Citations

  • Hydrophilic copolymer, and thermosetting composition and coating film containing the hydrophilic copolymer

    JP2018162431A